Theodiversity. [article]. - Norenzayan, Ara.
Humanity is teeming with breathtaking theodiversity-in religious beliefs, behaviors, and traditions, as well as in various intensities and forms of disbelief. Yet the origins and consequences of this diversity have received limited attention in psychology. I first describe how evolved psychological processes that influence and respond to cultural evolutionary trajectories generate and channel religious diversity. Next, I explore how theodiversity in turn shapes human psychology, and discuss three cultural dimensions of religious diversity in relation to psychological processes: (a) the cultural shift from small foraging bands and their local religios practices and beliefs to large and complex groups and their world religions, (b) cultural variability among world religions, and (c) secularization and the ensuring cultural divide between religious and nonreligious societies and subcultures. The contributions of psychology to the scientific study of religion will increase with a deeper understanding of theodiversity. -- (from the author)
Keywords: Atheism; WEIRD; Cognition; Cultural evolution; Culture; Gods; Religion; Ritual; Sacred values; Secularization; Supernatural beliefs; Theodiversity